Trade flows in a spatial oligopoly: Gravity works well, but what does it explain? - Alberto Salvo (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2006)
I begin by fitting traditional gravity equations to document that regional flows in the Brazilian cement industry exhibit gravity-like structure, with cement trade decaying sharply in distance traveled. I then show that this large distance effect owes to firms' strategic behavior over and above trade costs, with firm-level spatial supply decisions being characterized by the tacitly-collusive division (or sharing) of geographic markets. I am able to control for plant and trade costs thanks to an unusually disaggregated dataset, the simple production technology and a unique institutional setting. Thus, oligopoly can magnify the effects of distance. The paper suggests that trade theory, in its mission to explain the pattern of trade flows, should continue to advance in its modeling of strategic behavior in oligopoly. The paper also provides a rich and original example of a spatial cartel's pattern of supply. The tacit supply arrangement allows the cartel to sustain high prices, avoid large trade costs and, through the use of geography, potentially improve coordination.
Keywords: 330; Zementindustrie; Räumlicher Wettbewerb; Oligopol; Transaktionskosten; Gravitationsmodell; Wettbewerbsbeschränkung; Brasilien